Littérature et chanson, un dialogue stratégique pour la classe de français - Jean-Louis Dufays (Carnets)
This article aims to show that song constitutes a major learning issue for the study of literature in the French classroom because of the three fundamental links between it and literature: their relationship of reciprocal generation, their institutional convergences and the central, but differentiated, importance that they both accord to the text. The didactic study of the song, however, requires a specific analytical grid that both distinguishes and articulates the analysis of the text, the soundtrack and the visual performance. This triple grid is illustrated by the analysis of two songs, "Sur un prélude de Bach" by Maurane and "Carmen" by Stromae. The study leads to an integrated set of activity proposals that aim to thoroughly renew the teaching of French song.